Effect of free volume on cryogenic mechanical properties of epoxy resin reinforced by hyperbranched polymers. (April 2021) - Zhao, Yalin; Huang, Rongjin; Wu, Zhixiong; Zhang, Hua; Zhou, Zhengrong; Li, Laifeng; Dong, Yun; Luo, Mi; Ye, Bangjiao; Zhang, Hongjun
Abstract: Thermosetting polymer materials with excellent mechanical properties are highly promising in cryogenic engineering applications. However, the research on the toughening mechanism of thermosetting materials at cryogenic temperatures is always difficult. Herein, one type of high strength hyperbranched epoxy composite was successfully fabricated, and the correlation between microstructure (free volume) and mechanical properties of the HPB/epoxy composites was studied. To disclose the correlations between mechanical properties and microstructures for these composites, positron annihilation lifetime (PAL) measurements were carried out. Thereafter, better impact and compression properties were observed for composites with smaller free volume holes. Meanwhile, the impact and tensile properties of the composites are positively correlated with the free volume holes fraction at 77 K. The correlation between microstructure and mechanical properties provide valuable information for regulating the cryogenic mechanical properties of thermosetting materials in the future. Graphical abstract: Unlabelled Image Highlights: One type of high strength hyperbranched epoxy composite was successfully fabricated. The positron annihilation lifetime (PAL) measurements were carried out to detected the microstructure of hyperbranched epoxy composite. The effect of free volume holes on mechanical properties provide valuable information for improving the cryogenic mechanical properties of epoxy resins in future.